Human Adipose Tissue Metabolism in Obesity - Shuhao Lin; Michael D. Jensen (Journal of Obesity & Metabolic Syndrome)
The scientific understanding of adipose tissue has advanced tremendously during the past decade. Once thought to be an inert fat storage organ, we now know that adipose tissue serves important functions in energy balance and endocrinology, as well as playing a central role in the development of metabolic diseases. Adipose tissue lipid storage and lipolysis are tightly controlled by hormones, such as insulin, in response to the body’s energy needs. Adipose insulin sensitivity can be measured in vivo in humans using isotopic fatty acid tracers and the insulin clamp technique. These data allow investigators to calculate the plasma insulin concentration that results in a 50% suppression of lipolysis. In obesity, insulin’s action on adipose tissue lipolysis is clearly impaired, resulting in excess free fatty acids in circulation, which can lead to metabolic dysfunction. However, the cause of this impairment is unclear. The chronic, low-grade adipose tissue inflammation seen in obesity was thought to be the cause of adipose tissue insulin resistance. In this review, we discuss the structure of adipose tissue, how normal and abnormal adipose tissue metabolism contributes to metabolic diseases, and how inflammation might or might not play a role in adipose tissue insulin resistance.